Morphosyntactic processing in late second-language learners - Dowens, Margaret Gillon; Vergara, Marta; Barber, Horacio A.; Carreiras, Manuel (Massachusetts Institute of Technology Press (MIT Press), 2010)
The goal of the present study was to investigate the electro- physiological correlates of second-language (L2) morphosyn- tactic processing in highly proficient late learners of an L2 with long exposure to the L2 environment. ERPs were col- lected from 22 English–Spanish late learners while they read sentences in which morphosyntactic features of the L2 present or not present in the first language (number and gender agree- ment, respectively) were manipulated at two different sentence positions—within and across phrases. The results for a control group of age-matched native-speaker Spanish participants in- cluded an ERP pattern of LAN-type early negativity followed by P600 effect in response to both agreement violations and for both sentence positions. The late L2 learner results included a similar pattern, consisting of early negativity followed by P600, in the first sentence position (within-phrase agreement viola- tions) but only P600 effects in the second sentence position (across-phrase agreement violation), as well as significant am- plitude and onset latency differences between the gender and the number violation effects in both sentence positions. These results reveal that highly proficient learners can show electro- physiological correlates during L2 processing that are qualita- tively similar to those of native speakers, but the results also indicate the contribution of factors such as age of acquisition and transfer processes from first language to L2